A retrospective, multicenter study evaluating the prognostic value of minor salivary gland histology in a large cohort of patients with primary Sjögren's syndrome. (March 2015) - Carubbi, F; Alunno, A; Cipriani, P; Bartoloni, E; Baldini, C; Quartuccio, L; Priori, R; Valesini, G; De Vita, S; Bombardieri, S; Gerli, R; Giacomelli, R
Objective: The objective of this report is to investigate the prognostic value of minor salivary glands (MSG) assessment, routinely performed with hematoxilin-eosin (H&E) staining, for the diagnosis of primary Sjögren's syndrome (pSS). Methods: We retrospectively evaluated clinical, serological and histological features of 794 pSS patients. H&E-stained sections were assessed using the Chisholm and Mason grading system and/or the focus score (FS). Results: FS allowed the identification of a number of differences in the disease spectrum, and its prognostic role was further confirmed by quantifying the association between FS value and clinical/serological variables with binary logistic regression. Moreover, hypocomplementemia and FS resulted the only variables associated with lymphoma at univariate analysis, and FS appeared to be associated with lymphoma independently on complement fraction concentrations. Conversely, when patients were divided according to the Chisholm and Mason grading system, we failed to observe any significant difference between subgroups. Conclusion: In addition to its diagnostic role, our data seem to support that the routine assessment of MSG-FS with H&E staining is useful to predict at the time of diagnosis the adverse outcomes, such as lymphoma and extraglandular manifestations, that complicate the pSS course. On this basis, it should be recommended that an MSG biopsy be performed even in those patients displaying clinical and serological criteria, allowing the diagnosis of pSS independent of histological status.